Sejarah Kebangkitan dan Perkembangan Madrasah di Indonesia - Sobirin, Mad; Warisno, Andi; Ansori, Afif; Andari, An An; Syahfriadi, Syahfriadi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This research aims to reveal the role of Muslims in the establishment of madrasas in Indonesia, as well as the wider struggle for the spread of Islamic education in the country. The research method uses qualitative research that uses a historical methodological approach. Historical research is the methodical examination of records and other sources that contain information about the answers to historians' prehistoric questions. The results show that although the origin of madrasas in Indonesia has been the subject of much speculation, determining exactly when the name of the madrasa was first mentioned as a place of Islamic studies in Indonesia is still difficult to understand. However, it cannot be denied that madrasas or Islamic religious schools have appeared in Indonesia since the early 20th century. The conclusion obtained is that several Islamic groups, including Muhammadiyah, NU, and others, emerged in the early 20th century, coinciding with the rise of madrasas as places of teaching in Indonesia. The Ministry of Religion which was officially formed on 3 January 1946 had an important role in the growth of madrasas in the early years of independence. The politics of Islamic education in Indonesia is vigorously defended by this organization.